Pengembangan Literasi Bahasa Arab Santri melalui Pembelajaran Kitab Kuning di Lingkungan Pesantren - Asep Sunarko; Nurul Azizah (Al Jabiri: Jurnal Ilmiah Studi Islam, 2025)
This study aims to analyze the construction of students’ Arabic literacy through kitab kuning learning in the pesantren environment. This research employed a qualitative approach with a case study design conducted in three Islamic boarding schools: Nawwir Qulubana Islamic Boarding School, Safinnatun Naja Islamic Boarding School, and Nadhrotul Ulum Islamic Boarding School. The data were collected through observation, interviews, and documentation, then analyzed using a descriptive qualitative method through data reduction, data presentation, and conclusion drawing. The findings show that students’ Arabic literacy is formed through a gradual and repetitive process influenced by the learning culture of each pesantren. At Nawwir Qulubana, students’ literacy is developed through regular participation in kitab kuning learning activities. At Safinnatun Naja, literacy is strengthened through the understanding of nahwu and sharaf rules. Meanwhile, at Nadhrotul Ulum, literacy develops through discussion and peer learning among students. The methods of bandongan, sorogan, halaqah, and discussion play an important role in shaping students’ ability to read, understand, and interpret classical Arabic texts. This study concludes that kitab kuning learning is not only a pesantren scholarly tradition, but also a living literacy practice that contributes to the development of students’ Arabic language competence in a deeper way.